Peripheral monocyte transcriptional signatures of inflammation and oxidative stress in Parkinson’s disease - Thome, Aaron D.; Wang, Jinghong; Atassi, Farah; Thonhoff, Jason R.; Faridar, Alireza; Zhao, Weihua; Beers, David R.; Lai, Eugene C.; Appel, Stanley H. (Frontiers in Immunology, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by dopaminergic neuron loss in the substantia nigra, which is accompanied by immune dysfunction and chronic inflammation. Peripheral monocytes, key players in systemic inflammation, cross the blood-brain barrier and alter PD etiology and progression. To define the role of peripheral monocytes, cross-sectional studies of RNA transcripts isolated from PD monocytes were compared with age- and sex-matched control monocytes. After stratification by Hoehn & Yahr (H&Y) stage, inflammatory transcripts IL-6, IL-1β, ARG1, CD163, and CCR2 were upregulated in PD monocytes and increased with disease burden. Furthermore, PPARGC1A (PGC-1α), GPX4, NFE2L2 (NRF2), and SIRT3 decreased with increasing disease burden, while only SIRT1 expression increased, reflecting oxidative stress and mitochondrial dysregulation. Overall, the PD monocyte transcripts correlated with PD disease burden as monitored by H&Y, UPDRS total, UPDRS Part 3, ADL, and disease duration. This study demonstrated that dysregulation of inflammation and oxidative stress pathways contributed to disease progression in PD. Monocytes may serve as biomarkers for tracking clinical symptoms and could be leveraged as targets for therapeutic intervention.